2022
DOI: 10.1016/j.jceh.2021.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Pulmonary Aspergillosis and Tuberculosis Complicated by Hemophagocytic Lymphohistiocytosis - Sequelae of COVID-19 in a Liver Transplant Recipient

Abstract: Liver transplant recipients are at an increased risk of opportunistic infections due to use of immunosuppression. Coronavirus disease of 2019 (COVID-19) increases the risk of these infections further due to associated immune dysfunction and use of high dose steroids. We present a case of liver transplant recipient who developed disseminated tuberculosis and invasive pulmonary aspergillosis complicated by acquired hemophagocytic lymphohistiocytosis after recovering from severe COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“… 3 12 However, National Comprehensive Cancer Network guideline indicated that validated criterion to evaluate tumour response to molecular targeted therapies between the two criteria is needed. 13 Besides, several studies demonstrated that overall survival (OS) can be predicted more accurately by mRECIST than RECIST 1.1, since the latter is not capable of assessing therapy induced intratumoural necrosis. 14 15 On the contrary, another study observed both methods provided correlation with OS equally.…”
Section: Introductionmentioning
confidence: 99%
“… 3 12 However, National Comprehensive Cancer Network guideline indicated that validated criterion to evaluate tumour response to molecular targeted therapies between the two criteria is needed. 13 Besides, several studies demonstrated that overall survival (OS) can be predicted more accurately by mRECIST than RECIST 1.1, since the latter is not capable of assessing therapy induced intratumoural necrosis. 14 15 On the contrary, another study observed both methods provided correlation with OS equally.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our literature review, we encountered six cases of HLH secondary to aspergillosis with a mean age of ~47 years (Table 3) [8][9][10][11][12][13]. On her follow-up appointment after discharge, she was sent for HLH genetic analysis which tests for many genes involved in the pathogenesis of primary HLH, she did not have the test done (possibly due to the cost), and she did not follow up afterward.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was managed with intravenous immune globulin for HLH, liposomal Amphotericin B and ATT. 13…”
Section: Discussionmentioning
confidence: 99%